High hepatitis B surface antigen levels predict insignificant fibrosis in hepatitis B e antigen positive chronic hepatitis B. - Wai-Kay Seto (Public Library of Science (PLoS), 2012)
Introduction There is no data on the relationship between hepatitis B surface antigen (HBsAg) levels and liver fibrosis in hepatitis B e antigen (HBeAg)-positive patients with chronic hepatitis B (CHB). Methods Serum HBsAg and HBV DNA levels in HBeAg-positive CHB patients with liver biopsies were analyzed. The upper limit of normal (ULN) of alanine aminotransferase (ALT) was 30 and 19 U/L for men and women respectively. Histologic assessment was based on Ishak fibrosis staging for fibrosis and Knodell histologic activity index (HAI) for necroinflammation. Results 140 patients (65% male, median age 32.7 years) were recruited. 56 (40%) had ALT ≤2×ULN. 72 (51.4%) and 42 (30%) had fibrosis score ≤ 1 and necroinflammation grading ≤ 4 respectively. Patients with fibrosis score ≤ 1, when compared to patients with fibrosis score >1, had significantly higher median HBsAg levels (50,320 and 7,820 IU/mL respectively, p<0.001). Among patients with ALT ≤2×ULN, serum HBsAg levels achieved an area under receiver operating characteristic curve of 0.869 in predicting fibrosis score ≤ 1. HBsAg levels did not accurately predict necroinflammation score. HBsAg ≥ 25,000 IU/mL was independently associated with fibrosis score ≤ 1 (p=0.025, odds ratio 9.042).Using this cut-off HBsAg level in patients with ALT ≤2×ULN, positive and negative predictive values for predicting fibrosis score ≤ 1 were 92.7% and 60.0% respectively. HBV DNA levels had no association with liver histology. Conclusion Among HBeAg-positive patients with ALT ≤2×ULN, high serum HBsAg levels can accurately predict fibrosis score ≤ 1, and could potentially influence decisions concerning treatment commencement and reduce the need for liver biopsy.